Effect of Reimplanting Feedlot Heifers with Ralgro® and/or Synovex-H® - LaTourell, D.; Kuhl, Gerry L.; Drake, C. (Kansas State University. Agricultural Experiment Station, 2011)
Implanting heifers initially and mid-way through the finishing period with Ralgro and Synovex-H in any combination produced similar weight gains. Daily gains of cattle implanted with Ralgro + Ralgro, Ralgro + Synovex-H, Synovex-H + Ralgro and Synovex-H + Synovex-H were 3.66, 3.61, 3.66 and 3.75 lbs, respectively.
Keywords: Beef; Reimplanting; Heifers; Gain